Section 5: Patient Safety and Quality Assurance 2021
DOI: 10.1136/ejhpharm-2021-eahpconf.303
|View full text |Cite
|
Sign up to set email alerts
|

5PSQ-184 Knowledge and attitude assessment of pharmacists toward telepharmacy in Riyadh City, Saudi Arabia

Abstract: and the results are expressed as means± SD for continuous variables and as percentages (%) for categorical variables. Results 71 patients (53.3% women, mean age 82.7±6.7 (58-94) years) were treated with an AChEI. 74.6% (53 patients) were simultaneously treated with a DAP. Mean concomitant prescribed drugs (DAP and non-DAP) was 11.6±4.7 drugs (2-26). Prescribed AChEI were rivastigmine 56.3%, donepezil 38% and galantamine 5.6%. According to the classification of the systematic review of Durán et al, 71 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
7
2
Order By: Relevance
“…The finding of this study revealed that 32.4% (95% CI = 27%-37%) of pharmacy students had adequate knowledge regarding telepharmacy. The result of this study is lower as compared with studies conducted in Malaysia 67% [ 4 ], Saudi Arabia 42% [ 19 ], and the United States of America 60% [ 8 ]. The significant disparity could be attributed to the fact that developing countries use fewer eHealth applications than middle-income and developed countries [ 20 , 21 ].…”
Section: Discussioncontrasting
confidence: 81%
“…The finding of this study revealed that 32.4% (95% CI = 27%-37%) of pharmacy students had adequate knowledge regarding telepharmacy. The result of this study is lower as compared with studies conducted in Malaysia 67% [ 4 ], Saudi Arabia 42% [ 19 ], and the United States of America 60% [ 8 ]. The significant disparity could be attributed to the fact that developing countries use fewer eHealth applications than middle-income and developed countries [ 20 , 21 ].…”
Section: Discussioncontrasting
confidence: 81%
“…Previous research has demonstrated that telepharmacy reduces travel costs and saves time, which are considered a major barrier to patients in rural and distant settings, particularly the disabled and elderly, receiving healthcare services [ 4 , 9 ]. More than 91% of pharmacists in Alanazi et al’s study considered that employing a telepharmacy system may save them time and money [ 17 ]. The beneficial effect of telepharmacy in conserving patients’ resources was evaluated positively by study participants, with 91 percent agreement [ 18 ], according to Elnaem et al…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies about the knowledge, perception, and willingness of the public to use telepharmacy services. Nonetheless, there are no studies on the knowledge, perceptions, and readiness of hospital pharmacists about telepharmacy in Saudi Arabia, except in one conference abstract [ 17 ]. So, the present study included pharmacists who are working in hospital pharmacies.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 62.3% of participated pharmacists achieved good level of knowledge, which was higher than the finding from a Saudi Arabian study in 2021 (58%). 24 The reason for the above difference may be related to different sample sizes and evaluation methods. The percentage of pharmacists who meet the requirements of attitude toward using telepharmacy was 74.2%, in line with their readiness and active interest in the use of telepharmacy in pharmacy practice.…”
Section: Discussionmentioning
confidence: 99%